Targeted inhibition of HER-2 positive breast cancer cells by trastuzumab functionalized pullulan-doxorubicin nanoparticles. (September 2022) - Xu, Ruiling; Sui, Junhui; Zhao, Mingda; Yang, Yuedi; Tong, Lei; Liu, Yongmei; Sun, Yong; Fan, Yujiang; Liang, Jie; Zhang, Xingdong
Abstract: Human epidermal growth factor receptor-2 (HER-2) positive breast cancer is highly invasive with poor clinical outcomes and high risk of recurrence. Here, trastuzumab functionalized pullulan-doxorubicin nanoparticles (Tz-P-Dox) were developed and characterized as a new anticancer formulation for active targeting HER-2 overexpression of breast cancer cells. The obtained nanoparticles had the hydrodynamic diameter of 66.7 ± 2.0 nm and PDI of 0.218 ± 0.012. And the in vitro results showed significant difference of cell uptake and cytotoxic effect between Tz-P-Dox and non-targeted P-Dox against HER-2 positive cell lines (BT474 and MCF-7 cells). However, the differences between Tz-P-Dox and P-Dox were not observed in HER-2 negative cell lines (MDA-MB-231 cells). These results suggested that trastuzumab functionalized nanoparticles had great potential to be considered as a candidate drug for HER-2 positive breast cancer treatment. Highlights: Tz-P-Dox was synthesized for active targeting HER-2 overexpression of breast cancer cells. Tz-P-Dox had suitable size and narrow size distribution (66.7 ± 2.0 nm). The expression of HER-2 was high, medium and low in BT474, MCF-7 and MDA-MB-231 cells, respectively. Tz-P-Dox exhibited significant difference in cell uptake and cytotoxic effect.